Examining the undergraduate student experience of transgender students at small, private, liberal arts institutions: a phenomenological analysis - Newhouse, Ben J., author; Kuk, Linda, advisor; Carlson, Laurie, committee member; DeMirjyn, Maricela, committee member; Miller, Lisa, committee member (Colorado State University. Libraries, 2021)
As the population of students who identify as transgender grows on college campuses, it is critical that higher education identify the ways in which institutions can more effectively serve the needs of this population, creating an environment that is supportive and inclusive. The literature demonstrates that campuses have fallen short of this goal. This study was designed to understand the lived experiences of seven transgender students who matriculated at small, private, liberal arts institutions in the south and southeast. By understanding their lived experiences, institutions that are truly committed to creating an environment that is diverse, equitable, and inclusive can understand common areas where institutions fall short and understand the ways in which participants experienced support and inclusion in meaningful ways during their time as undergraduates.
Keywords: gender identity; university; transgender; college